2019
DOI: 10.1371/journal.pone.0223687
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with peer support for breastfeeding in Beirut, Lebanon: A qualitative study

Abstract: BackgroundDespite the beneficial effects of peer support on breastfeeding, research on the process of peer support is scarce. In Lebanon, exclusive breastfeeding is only 15% in infants below six months. A multidisciplinary team launched a multi-component breastfeeding support intervention, with peer support, and professional lactation support provided by International Board Certified Lactation Consultants (IBCLs) to target this decline.AimTo describe the experiences of breastfeeding mothers and peer support pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 17 publications
1
19
0
10
Order By: Relevance
“…A recent trial by our group revealed that mothers who received a multi-component breastfeeding intervention consisting of breastfeeding education by a lactation expert, peer, and professional lactation support were six times more likely to practice exclusive breastfeeding for six months, as compared to standard care [29]. Whereas peer support was viewed by the trial's participants as important in encouraging them to continue breastfeeding, lactation expert support was considered influential in helping them solve technical problems with breastfeeding [30]. Although the presence of certified lactation consultants is recommended by the Ministry of Public Health, this recommendation is not a requirement by the government for hospital accreditation.…”
Section: Plos Onementioning
confidence: 98%
“…A recent trial by our group revealed that mothers who received a multi-component breastfeeding intervention consisting of breastfeeding education by a lactation expert, peer, and professional lactation support were six times more likely to practice exclusive breastfeeding for six months, as compared to standard care [29]. Whereas peer support was viewed by the trial's participants as important in encouraging them to continue breastfeeding, lactation expert support was considered influential in helping them solve technical problems with breastfeeding [30]. Although the presence of certified lactation consultants is recommended by the Ministry of Public Health, this recommendation is not a requirement by the government for hospital accreditation.…”
Section: Plos Onementioning
confidence: 98%
“…Metode penelitian yang teridentifikasi dari artikel menunjukkan 8 artikel merupakan penelitian kuantitatif, 3 artikel merupakan penelitian kualitatif, dan 1 artikel merupakan report article. Artikel -artikel dalam studi ini berupa retrospective study (n=1), (13) descriptive study (n=1), (14) randomized controlled trial (n=4), (15)(16)(17)(18) Secondary data analysis (n=1) menggunakan data dari program Breastfeeding Peer Counselor (BFPC), (19) qualitative study (n=3), (20)(21)(22) education report article (n=1), (23) serta randomized clinical trial (n=1). (24) Tabel 2.…”
Section: Metodeunclassified
“…Penelitian di Lebanon mengungkap bahwa dukungan sebaya memberikan kepuasan bagi ibu terhadap pengalaman menyusui mereka dan sangat menghargai dukungan yang diberikan oleh rekan-rekan mereka dan juga International Board Certified Lactation Consultants (IBCLCs). (20) Lebih lanjut diungkapkan bahwa dukungan sebaya dianggap penting dalam mendorong kelanjutan menyusui, sedangkan dukungan IBCLCs berpengaruh dalam pemecahan masalah. (20) Martinez-Brockman et.al (2019) dalam penelitiannya menyatakan bahwa konselor sebaya mendorong para ibu yang mengalami kesulitan, mendukung keberhasilan, dan memberikan dukungan dan bimbingan melalui pesan teks ataupun tatap muka jika memungkinkan.…”
Section: Hasilunclassified
See 2 more Smart Citations